Role of Science & Technology, Higher Education and Research in Regional Socio-Economic Development - Rajesh Shukla Preeti Kakar (National Council of Applied Economic Research, 2006)
This paper is an attempt to focus on the role of Science and Technology (S&T) on regional development of India by considering 21 Indian states. The Index approach using the Principal Component technique has been adopted. For analysing the impact, a set of three indices focussing on Current Economic Status, S & T and Welfare has been calculated. Further, using the S&T Index as the basis, the states have been classified into four major categories. Inter and intra-group comparisons are discussed